Relation Hepcidin with Renal Failure - Ali, Dr. Rusul Arif Abd (Medical Science Journal for Advance Research, 2020)
Renal failure refers to a condition where the kidneys lose their normal functionality, which may be due to various factors including infections, auto immune diseases, diabetes and other endocrine disorders, cancer, and toxic chemicals. It is characterized by the reduction in the excretory and regulatory functions of kidney. Biochemically, it is typically detected by an elevated serum creatinine. In the science of physiology it is described as a decrease in glomerular filtration rate (GFR). Hepcidin is a peptide produced primarily in the liver. Its mature form consists of 25 amino acids with a calculated mass of 2.8 kDa . Hepcidin has a key role in iron homeostasis by interacting with ferroportin. Hepcidin is the regulator of iron homeostasis in humans and other mammals. In humans, HAMP is the gene that encodes for hepcidin. 25-amino acid peptide was first identified in human urine and plasma. This peptide contains four disulfide bonds. It is synthesized, processed and secreted primarily by hepatocytes. In vitro, human hepcidin has anti-bacterial and antifungal activities. The 25-amino acid peptide of hepcidin is secreted by the liver, which seems to be the "master regulator" of iron metabolism.